Friends mechanism-based routing intrusion detection model for mobile ad hoc network - Yang XIAO; Lei BAI; Xian WANG (Tongxin xuebao)
The proposed model mainly focused on how to effectively detect routing invasions from mobile ad hoc network as well as how to accurately respond to the malicious nodes,providing a trusted routing environment.A lightweight intrusion detection model was proposed to based on the friends mechanism,taking black hole attack for example,the OPNET software gives the simulation test,and results show that the schemes can effectively detect attacks,it is validated and compared with other conventional models.